2012
DOI: 10.1016/j.jmp.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Phase-oscillator computations as neural models of stimulus–response conditioning and response selection

Abstract: The activity of collections of synchronizing neurons can be represented by weakly coupled nonlinear phase oscillators satisfying Kuramoto's equations. In this article, we build such neural-oscillator models, partly based on neurophysiological evidence, to represent approximately the learning behavior predicted and confirmed in three experiments by well-known stochastic learning models of behavioral stimulus-response theory. We use three Kuramoto oscillators to model a continuum of responses, and we provide det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(56 citation statements)
references
References 55 publications
1
55
0
Order By: Relevance
“…Evidence from many studies suggests that phase modulation or phase synchronization can be the mechanism underlying the neural activities relative to the cognitive processes of language and memory retrieval (21,22). Given what we know about the phase locking or synchronization of oscillators (23,24), the synchronization of phases is conjectured to be the physical mechanism of retrieval. An unknown sound reaching the cortex is recognized as the specific spoken syllable /pi/ by the synchronization of its phase pattern with the stored phase pattern of /pi/ in verbal memory.…”
mentioning
confidence: 99%
“…Evidence from many studies suggests that phase modulation or phase synchronization can be the mechanism underlying the neural activities relative to the cognitive processes of language and memory retrieval (21,22). Given what we know about the phase locking or synchronization of oscillators (23,24), the synchronization of phases is conjectured to be the physical mechanism of retrieval. An unknown sound reaching the cortex is recognized as the specific spoken syllable /pi/ by the synchronization of its phase pattern with the stored phase pattern of /pi/ in verbal memory.…”
mentioning
confidence: 99%
“…Because transparallel processing by hyperstrings provides classical computers with quantum power, it strengthens ideas that quantum-like cognitive processing does not have to rely on actual quantum mechanical phenomena at the subneuron level (de Barros and Suppes 2009;Suppes et al 2012;Townsend and Nozawa 1995;Vassilieva et al 2011). Instead, as I argued, it might rely on interactions at the level of neurons.…”
Section: Discussionmentioning
confidence: 52%
“…In searching for an appropriate neural synchronization mechanism several theoretical models have been developed (Malsburg, 1995;Jalili, 2009;Suppes et al, 2012;Vassilieva et al, 2011;Zavaglia et al, 2012;Burwick, 2014;Raffone & Van Leeuwen, 2001b). These models have shown that employing synchronization it is possible to perform various types of computing.…”
Section: Synchronization and Binding Problemmentioning
confidence: 99%